Aplikasi Website Pemetaan Penyakit Demam Berdarah Menggunakan Metode Geographically Weighted Regression untuk Memprediksi Tingkat Penyebarannya di Surabaya - Holiyed Hadi; Andreas Handojo; Siana Halim (Jurnal Infra, 2020)
Dengue Fever is the one of the most popular endemic illness in Indonesian.. In early 2019, East Java was recorded as the province with the most Dengue Fever cases in Indonesia, because of that the prevent action is needed to reduce the Dengue Fever cases in East Java. But, due to limitations to get East Java data, this research uses Surabaya data as a model, because it has more complete data.The aim of this research is mapping the Dengue Fever with Geographically Weighted Regression (GWR) method that give a local weighted in every independence variable such as rainfall, the number of rainy day in a year, temperature, and humidity, so that can give the more accurate output to prevent Dengue Fever in future.The Output of this research is Mapping with color that based on the distribution rate of  Dengue Fever in every puskesmas area in Surabaya, along with mapping the weights of each independent variable to determine which independent variable influences the determination of dengue fever patients in every puskesmas area in Surabaya. So that area, can do a prevent action from the output of this research.